2014
DOI: 10.1007/s10549-014-3188-z
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression profiling to predict the risk of locoregional recurrence in breast cancer: a pooled analysis

Abstract: The 70-gene signature (MammaPrint) has been developed to predict the risk of distant metastases in breast cancer and select those patients who may benefit from adjuvant treatment. Given the strong association between locoregional and distant recurrence, we hypothesize that the 70-gene signature will also be able to predict the risk of locoregional recurrence (LRR). 1,053 breast cancer patients primarily treated with breast-conserving treatment or mastectomy at the Netherlands Cancer Institute between 1984 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…In addition, as an alternative to whole breast irradiation partial breast irradiation is currently studied, since most of the local recurrences occur at or near the tumor bed [42]. Further, in decision making for the use of RT the biological background of breast cancer may play a role [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as an alternative to whole breast irradiation partial breast irradiation is currently studied, since most of the local recurrences occur at or near the tumor bed [42]. Further, in decision making for the use of RT the biological background of breast cancer may play a role [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the mastectomy group, the signature was evaluated separately in patients treated with and without post-mastectomy radiotherapy (PMRT). Those treated with PMRT and classified as high risk experienced more LRR at 10 years (LRR 11.0% high risk versus 3.1% low risk, P ¼ 0.004), whereas in patients who did not receive PMRT, classification as high or low risk did not affect LRR (LRR 12.9% high risk versus 9.2% low risk, P ¼ 0.302) [31]. Although the signature was predictive of LRR exclusively in radiotherapy treated patients in the mastectomy subgroup, high-risk classification by MammaPrint Ò was also shown to be an independent prognostic factor for LRR in the entire cohort and has already been proven to identify patients at high risk of distant metastasis [21].…”
Section: Mammaprint òmentioning
confidence: 98%
“…57,58 Speer and colleagues 59 developed a molecular signature for radiation response in breast cancer that is enriched for biologic concepts implicated in response to radiation therapy, including DNA damage repair and cell cycle regulation. They suggested that their signature outperforms previous signatures and may more accurately stratify the likelihood of local recurrence of breast cancer.…”
Section: Predictive Markers For Local Recurrences After Bct?mentioning
confidence: 99%